A population‐based study of metastatic colorectal cancer in individuals aged ≥80 years. Issue 4 (18th September 2012) - Kumar, Rajiv; Jain, Kunal; Beeke, Carol; Price, Timothy J.; Townsend, Amanda R.; Padbury, Rob; Roder, David; Young, Graeme P.; Richards, Alison; Karapetis, Christos S.
Abstract BACKGROUND. Life expectancy is increasing, and more patients are presenting with cancer at an advanced age (≥80 years). Optimal management for this group of patients has not been well defined. METHODS. The South Australian Clinical Registry for Metastatic Colorectal Cancer (mCRC) collects data on all patients diagnosed since February 2006 in South Australia. The authors examined cancer characteristics, treatments administered, and outcomes for patients aged ≥80 years compared with patients aged <80 years. RESULTS Data from 2314 patients were evaluable, and 29.2% of these patients were aged ≥80 years. The majority had moderately differentiated tumors. Poorly differentiated tumors were reported in fewer patients aged ≥80 years (20.1% vs 26.1%; P < .005). Overall, 28.1% of patients aged ≥80 years received chemotherapy, and 74.2% received single‐agent fluoropyrimidines as first‐line treatment. By comparison, 68.2% of patients aged <80 years received chemotherapy, 74.3% received combination chemotherapy, and 25.7% received single‐agent fluoropyrimidine as first‐line treatment. No treatment was received by 38.2% of patients aged ≥80 years compared with 11.4% of those aged <80 years. Participation in clinical trials was lower in patients aged ≥80 years (2% vs 13%). The median survival was worse for patients aged ≥80 years (8.2 months vs 19.2 months; P < .001), and the median survival of patients who received chemotherapy was 19.0 months for those aged ≥80 years and 22.3 months for those aged <80 years (P = .139). Patients who did not receive treatment had a poor median survival regardless of age (2.6 months for patients aged ≥80 years vs 2.7 months for patients aged <80 years). CONCLUSIONS. Patients aged ≥80 years were less likely to receive intervention for their metastatic colorectal cancer and had poorer survival. The survival of selected patients aged ≥80 years who received chemotherapy was similar to the survival of those aged <80 years despite the receipt of single‐agent therapy. Patients aged ≥80 years with metastatic colorectal cancer are less likely to receive intervention for their disease and have poorer survival. Survival for selected patients aged ≥80 years who receive chemotherapy is similar to the survival of patients aged <80 years despite the receipt of single‐agent therapy. Cancer 2013. © 2012 American Cancer Society.